PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GENIALLY BERBANTUAN CANVA PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI HAK DAN KEWAJIBAN DI SEKOLAH KELAS III SDN 1 JEPUN KABUPATEN TULUNGAGUNG - Yenny Retno Wilujeng; Rahmad Setyo Jadmiko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Media serves as a tool for conveying information to students, enabling them to grasp the material effectively. The use of media that integrates visual, audio, and interactive elements can help students achieve a deeper understanding of concepts. This study aims to transform the learning process by fostering student engagement through the use of interactive media specifically Genially combined with Canva with the ultimate goal of creating an interactive learning experience, particularly for the Pancasila Education subject. This research and development study was conducted at SDN 1 Jepun, Tulungagung Regency, employing the Research and Development (R&D) method based on the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The product resulting from this study is an interactive medium designed to support learning activities. The average percentage score from the two media validators was 94% (categorized as "highly valid") based on trials conducted with third-grade students at SDN 1 Jepun. Meanwhile, the average percentage score from the two subject matter experts was 91% (categorized as "highly valid"). Questionnaire analysis revealed average student response rates of 86.8% for the small-group trial and 89.8% for the large-group trial, both falling into the "excellent" category. Additionally, teacher responses yielded a score of 94%, also categorized as "excellent." The results presented above demonstrate that the developed interactive learning medium possesses a high level of applicability and is easy to use in teaching and learning activities furthermore, this medium assists teachers in facilitating more meaningful learning and helps broaden the student knowledge.